Zn-Mo/HZSM-5 Catalyst for Gasoil Range Hydrocarbon Production by Catalytic Hydrocracking of Ceiba pentandra oil - Yustia Wulandari Mirzayanti; Firman Kurniawansyah; Danawati Hari Prayitno; Achmad Roesyadi (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Biofuel from vegetable oil becomes one of the most suitable and logical alternatives to replace fossil fuel. The research focused on various metal ratio Zinc/Molybdenum/HZSM-5 (Zn-Mo/HZSM-5) catalyst to produce liquid hydrocarbon via catalytic hydrocracking of Ceiba penandra oil. The catalytic hydrocracking process has been applied in this study to crack Ceiba pentandra oil into a gasoil range hydrocarbon using Zn-Mo/HZSM-5 as a catalyst. The effect of various reaction temperature on the catalytic hydrocracking of Ceiba pentandra oil were studied. The Zn-Mo/HZSM-5 catalyst with metal ratio was prepared by incipient wetness impregnation method. This process used slurry pressure batch reactor with a mechanical stirrer. A series of experiments were carried out in the temperature range from 300-400 oC for 2 h at pressure between 10-15 bar. The conversion and selectivity were estimated. The liquid hydrocarbon product were identified to gasoline, kerosene, and gas oil. The results show that the use of Zn-Mo/HZSM-5 can produce gas oil as the most component in the product. Overall, the highest conversion and selectivity of gas oil range hydrocarbon was obtained when the ZnMo/HZSM-5 metal ratio was Zn(2.86 wt.%)-Mo(5.32 wt.%)/HZSM-5 and the name is Zn-Mo/HZSM-5_102. The highest conversion was obtained at 63.31 % and n-paraffin (gas oil range) selectivity was obtained at 90.75 % at a temperature of 400 oC. Ceiba pentandra oil can be recommended as the source of inedible vegetable oil to produce gasoil as an environmentally friendly transportation fuel.